PWE-301 Diagnostic accuracy of mri for assessment of t stage, lymph node metastases, and circumferential resection margin involvement in patients with rectal cancer: a single institution experience. (22nd June 2015) - Liao, CCL; Lacey, N; Cresner, R; Wynn, G
Abstract : Introduction: Magnetic resonance imaging (MRI) is an established modality in local staging of primary rectal cancer. 1 Its use has been employed to assess operability for locally advance rectal cancer, or suitability for adjuvant chemo radiotherapy in the light of involved circumferential resection margin (CRM) or involved levator sphincter complex. 2 The purpose of this study was to determine the accuracy of high resolution MRI scan for t-staging, lymph node metastasis and CRM involvement in primary rectal cancer, in a single institution. Method: Retrospective analyses of data collected from a series of prospectively treated patients diagnosed with rectal cancer from June 2010 to May 2013 was performed, who underwent surgery without adjuvant chemotherapy or chemo-radiotherapy. MRI scan staging was compared with final histology. Two reviewers, each for radiology and histology independently extracted the data. A third reviewer to determine the accuracy then compared both staging. Results: Total of one hundred and seventy seven patients was diagnosed with rectal cancer between the specified time periods. Only seventy-five patients went straight to surgery, as fifty-three of them needed some form of adjuvant treatment. Another forty-nine did not have surgery or were unsuitable for surgical resection. Out of seventy-five patients, there were fifty-two male and twenty-three female patients. Median age was 73 years. Accuracy of MRI for t staging was 70%, for lymph node metastasis it was 71% and for CRM involvement it was 92% respectively. Within different t stages, MRI over staged T1/T2, T3 and T4 tumours by 3.2%, 28.5% and 33.3% respectively, compared to histology. Similarly MRI under staged T1/T2, T3 and T4 tumours by 16%, 4.8% and 33.3% respectively. The accuracy of MRI in assessing different t stages was 80% for T1/T2 tumours, 65.8% for T3 tumours, and 33.3% for T4 tumours. Conclusion: MRI has good accuracy for assessing CRM involvement, which is most important in deciding pre-operative, adjuvant chemo radiotherapy. T staging and lymph node assessment is not as good. Disclosure of interest: None Declared. References: Ann Surg Oncol . 2012;19(7):2212-23. doi: 10.1245/s10434-011-2210-5. Epub 2012 Jan 20 Dis Colon Rectum . 2015;58(3):275–82. doi: 10.1097/DCR.0000000000000250